Prescribing Errors in an Ambulatory Care Setting: Mitigating Risks in Outpatient Medication Orders, Cross-Sectional Review - Wesam S. Abdel-Razaq; Ghada Mardawi; Aiman A. Obaidat; Lama Aljahani; Maram Almutairi; Reham Almotiri; Nataleen A. Albekairy; Tariq Aldebasi; Abdulkareem M. Albekairy; Mohammad S. Shawaqfeh (Global Journal on Quality and Safety in Healthcare, 2024)
Introduction Prescribing errors (PEs) are the most common type of medication error, which may occur by prescribing the wrong medication, improper dose, dosage, and/or even prescribing a drug to the wrong patient. The present study aims to compile PEs that were generated in an ambulatory care setting at a tertiary-care hospital in Saudi Arabia. Methods A retrospective cross-sectional review was conducted for all reported PEs in ambulatory care clinics for 3 years. The potential hazardous outcomes of these PEs were classified according to the medication error index. Results A total of 897 records containing 1199 PEs were retrieved. More than a third of prescribers had frequently committed PEs—ranging from 2 to 39 times. The most encountered errors were prescribing incorrect doses, medication duplication, incorrect dosing frequency, and inappropriate duration (34.5%, 14.1%, 11.6%, and 9.8%, respectively). The most frequent mistakes were when prescribing antibiotics (22.9%) and drugs for cardiovascular conditions (18.5%). Most errors were of mild to moderate severity, mostly type-B near-miss errors and did not reach patients. Only two prescription events (0.17%) had severe consequences that required intervention to avoid any subsequent harm or damage. Conclusion The current investigation has revealed a substantial percentage of PEs, mostly in internal medicine and cardiology departments. Although PEs are undoubtedly not easy to avoid, monitoring and recognizing these inaccuracies is pivotal to preventing potential harm and promoting patient safety.